P-702 Centrifugal Pump Damage Analysis Insights and Implications: P-702 Analisis Kerusakan Pompa Sentrifugal Wawasan dan Implikasi - Abdullah Barafi, Keigen; Fahruddin, A’rasy (Procedia of Engineering and Life Science, 2024)
Centrifugal pumps are widely used in industries for fluid transfer, operating on the rotation of an impeller driven by a prime mover. However, sudden performance drops and operational instability pose significant challenges, impacting overall system efficiency. Predictive maintenance relies on vibration analysis to assess rotating equipment condition, with vibration patterns indicating potential issues such as cavitation and corrosion. Prolonged cavitation leads to erosion of channel wall surfaces, resulting in structural damage. This study aims to address the knowledge gap in understanding the relationship between pump vibration, cavitation, and corrosion. Through comprehensive vibration analysis and examination of pump performance, our research identifies the mechanisms driving pump degradation. The findings highlight the critical role of predictive maintenance in mitigating pump failures and optimizing system performance. Highlights : Vibration analysis crucial for predictive maintenance: Identifying early signs of pump deterioration. Cavitation-induced erosion: Understanding the impact of prolonged cavitation on pump performance. Importance of proactive maintenance: Mitigating pump failures and optimizing system efficiency. Keywords : Centrifugal pumps, Vibration analysis, Cavitation, Corrosion, Predictive maintenance